(untitled) (International Journal of Engineering and Computer Science, 2024)
This research paper explores the transformative role of predictive analysis in healthcare, with a specific focus on predicting and managing Parkinson’s disease as a case study. By integrating advanced analytics and machine learning techniques, we delve into the intricate landscape of healthcare data to forecast patient outcomes, optimize resource allocation, and enhance overall healthcare decision-making. Through an exhaustive examination of literature and scientific inquiry, we illuminate the promising applications of predictive analysis in addressing the chronic and complex nature of neurodegenerative diseases like Parkinson’s. The paper also discusses the challenges, ethical considerations, and future directions within the realm of predictive analysis in healthcare, offering a comprehensive perspective on its potential to revolutionize patient care and public health outcomes.